2023
DOI: 10.3390/diagnostics13101755
|View full text |Cite
|
Sign up to set email alerts
|

Artificial-Intelligence-Driven Algorithms for Predicting Response to Corticosteroid Treatment in Patients with Post-Acute COVID-19

Abstract: Pulmonary fibrosis is one of the most severe long-term consequences of COVID-19. Corticosteroid treatment increases the chances of recovery; unfortunately, it can also have side effects. Therefore, we aimed to develop prediction models for a personalized selection of patients benefiting from corticotherapy. The experiment utilized various algorithms, including Logistic Regression, k-NN, Decision Tree, XGBoost, Random Forest, SVM, MLP, AdaBoost, and LGBM. In addition easily human-interpretable model is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Compared to our previous work [35] , this approach has improved the capability of CS treatment prediction for more than 6% accuracy. Here, it can be concluded that additional information, such as CXR is useful in CS treatment prediction.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Compared to our previous work [35] , this approach has improved the capability of CS treatment prediction for more than 6% accuracy. Here, it can be concluded that additional information, such as CXR is useful in CS treatment prediction.…”
Section: Resultsmentioning
confidence: 83%
“…The metrics used are accuracy, precision, recall, balanced accuracy, and F1-score, which are usually used in evaluating classification tasks. The definitions of the mentioned metrics are shown below [35] : 1 2 where TN – number of True Negative cases, TP – True Positives, FP – False Positives, FN – False Negatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible approach to improve clinical decision making may be the use of artificial intelligence driven algorithms, as demonstrated by an affiliated collective of Myska et al [ 34 ], who have used the data from Olomouc post-COVID dataset to test the performance of 9 different machine learning algorithms in predicting improvement in the patients indicated for CS therapy. The best results were achieved by the Decision Tree approach, reaching 73.52% balanced accuracy on a validation portion of the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…As far as possible, when sensors and/or AI are used, there should be a document precisely defining the responsibility of each participant. For example, remote telemonitoring has been widely used during the COVID-19 pandemic in order to obtain early hospital discharge, allowing beds to be saved for other patients, and it will again be used to follow the numerous patients suffering from long COVID [ 11 , 67 , 68 , 69 ]. This is a simple use case, but doctors would have been responsible if one parameter (blood saturation decrease related to worsening of pneumopathy secondary to virus spreading) were not to be detected or not transmitted early enough to the doctor.…”
Section: Discussionmentioning
confidence: 99%